Literasi Teknologi Informasi Komunikasi Peserta Pelatihan Desain Grafis Balai Latihan Kerja Kota Pekalongan - Muchammad Chulailul Afda; Monika Pretty Aprilia (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
A graphic designer, in addition to having the abilities he has, should have several abilities such as a good attitude at work, sensitivity in solving problems, creativity and broad insight, responsibility, and literacy in Information and Communication Technology (ICT). Because with good ICT literacy, graphic designers will find it easy to get sources of information that increase competence in the design process and can make maximum use of technology. This study aims to see how ICT literacy knowledge in the graphic design field of Pekalongan Graphic Design BLK participants uses 7 elements belonging to the 21st Century ICT Literacy Model, namely defining, accessing, evaluating, managing, integrating, creating, and communicating. This study uses a qualitative approach. Data collection was carried out by conducting interviews and observations on three graphic design training participants at the Pekalongan City BLK. From the research that has been done, it can be concluded that one of the three participants of the Pekalongan City BLK training majoring in Graphic Design does not have one of the elements of ICT literacy, namely integrating. Also, in the design process, there are still some obstacles in the language of the tools, the internet, and devices such as laptops that suddenly crash and are full of memory.